2021
DOI: 10.1007/s00432-021-03867-1
|View full text |Cite
|
Sign up to set email alerts
|

Low blood levels of high-density lipoprotein (HDL) cholesterol are positively associated with cancer

Abstract: Purpose There is a growing body of evidence suggesting a decisive involvement of the human lipid metabolism in cancer development. However, clinical data on the association between blood triglyceride or cholesterol levels including the cholesterol transporters high-density and low-density lipoproteins (LDL, HDL) and cancer incidence have remained inconclusive. Here, we investigated the association between blood triglyceride as well as total, LDL and HDL cholesterol levels and cancer among outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…We acknowledge the fact that our study is limited by various aspects, most of which are due to the chosen study design and cannot be avoided [ 13 , 28 , 29 ]. Most importantly, diagnoses within our databank are recorded as ICD-10 codes, which might be associated with the misclassification of certain diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We acknowledge the fact that our study is limited by various aspects, most of which are due to the chosen study design and cannot be avoided [ 13 , 28 , 29 ]. Most importantly, diagnoses within our databank are recorded as ICD-10 codes, which might be associated with the misclassification of certain diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 highlights that overweight patients have more concomitant disease than patients with normal body weight. Finally, subgroup analyses of individual cancer sites or subtypes (e.g., left/right sided colorectal cancer) were not feasible due to the small sample sizes, which might be associated with a presentation bias, as recently described in detail [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge the fact that our study is subject to various limitations, most of which are due to the chosen study design and cannot be avoided (Labenz et al 2020a ; Loosen et al 2021 ; Roderburg et al 2021 ). Most importantly, diagnoses within our database are coded as ICD-10 codes, which might be associated with the misclassification of certain diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of general and specialized practices in Germany [ 4 ]. Finally, this database has already been used in previous studies focusing on cancer [ 5 , 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%